Application for Testing Smart Meters - Kohout, David (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2022)
This paper presents our developed application for smart metering, which we are using to test the interoperability of different smart meters, compatibility with transmission technologies, to measure data volumes, test data security, and also ensure data security through the whole life-cycle of smart meters. The paper concludes with future development and planned features of our application, which is already being used for testing smart metering technologies at the Smart Grid Lab at BUT.
Keywords: DLMS; electricity measuring; smart metering; testing application